Ofir spit (Portugal) - Santos-Ferreira, Alexandre (2017)
The Ofir spit is located at the estuary of Cavado River (NW coast of Portugal), and is the natural protection of Esposende city, ensuring also the navigability of the river and preventing from the maritime invasion of its estuary or the flooding of the riverine part of that city. It has been subjected to the actions of nature, especially from the Atlantic Ocean, known for its energetic regime and, more recently, those of human activities. Considering that, in Portugal, the use of geosynthetics on coastal protection is not yet a usual solution, it is relevant to investigate it, especially in this case of high-energy wave agitation. The paper presents a summary on the interventions conducted to the sandbank along time, it refers also the solution implemented as well as the monitoring campaign conducted after December 2015, discussing its results and the viability of the structure itself as a permanent solution.